mTOR-regulated translation during first the wave of inner cell generation in mouse preimplantation embryos - Černá, Pavlína (Jihočeská univerzita, 2022)
The aim of this master thesis was to investigate the role of mTOR and connected pathways in early mouse preimplantation development.
mTOR-regulated translation during first the wave of inner cell generation in mouse preimplantation embryos
Keywords: mouse preimplantation development; trophectoderm; primitive endoderm; epiblast; mTOR signalling pathway; mouse preimplantation development; trophectoderm; primitive endoderm; epiblast; mTOR signalling pathway